ING1b negatively regulates HIF1α protein levels in adipose-derived stromal cells by a SUMOylation-dependent mechanism - Bigot, N (Cell Death Dis, 2015)
Hypoxic niches help maintain mesenchymal stromal cell properties, and their amplification under hypoxia sustains their immature state. However, how MSCs maintain their genomic integrity in this context remains elusive, since hypoxia may prevent proper DNA repair by downregulating expression of BRCA1 and RAD51. Here, we find that the ING1b tumor suppressor accumulates in adipose-derived stromal cells (ADSCs) upon genotoxic stress, owing to SUMOylation on K193 that is mediated by the E3 small ubiquitin-like modifier (SUMO) ligase protein inhibitor of activated STAT protein γ (PIAS4). We demonstrate that ING1b finely regulates the hypoxic response by triggering HIF1α proteasomal degradation. On the contrary, when mutated on its SUMOylation site, ING1b failed to efficiently decrease HIF1α levels. Consistently, we observed that the adipocyte differentiation, generally described to be downregulated by hypoxia, was highly dependent on ING1b expression, during the early days of this process. Accordingly, contrary to what was observed with HIF1α, the absence of ING1b impeded the adipogenic induction under hypoxic conditions. These data indicate that ING1b contributes to adipogenic induction in adipose-derived stromal cells, and thus hinders the phenotype maintenance of ADSCs.